Association between Irisin, hs-CRP, and Metabolic Status in Children and Adolescents with Type 2 Diabetes Mellitus. (20th March 2019) - Elizondo-Montemayor, Leticia; Gonzalez-Gil, Adrian M.; Tamez-Rivera, Oscar; Toledo-Salinas, Carla; Peschard-Franco, Mariana; Rodríguez-Gutiérrez, Nora A.; Silva-Platas, Christian; Garcia-Rivas, Gerardo
Abstract : Proinflammatory cytokines and the novel myokine irisin, a cleavage product of FNDC5, have been found to play a role in obesity and type 2 diabetes mellitus (T2DM). Irisin has been shown to increase browning of adipose tissue, thermogenesis, energy expenditure, and insulin sensitivity, yet its association with inflammatory markers is still limited. Circulating irisin has been found to be increased in obesity, while in adult subjects with T2DM decreased levels have been found. However, data establishing the association of circulating irisin in children and adolescents with T2DM has not been described in the literature. The objective of this study was to determine irisin plasma concentration and its association with metabolic and adiposity markers and with hs-CRP, a surrogate marker of inflammation used in clinical practice, in a pediatric population with T2DM. A cross-sample of 40 Mexican children and adolescents aged 7-17 were recruited, 20 diagnosed with T2DM and 20 healthy controls. Plasma irisin levels were found to be lower in the T2DM group compared with controls, which could be attributed to a reduced PGC-1 α activity in muscle tissue with a consequent decrease in FNDC5 and irisin expression. Irisin concentration was found to be positively correlated with HDL-c, LDL-c, and total cholesterol, while negatively correlated with BMI, waist circumference, and triglycerides. However, after multiple regression analysis, only HDL-c correlation remained significant. hs-CRP was higher in the T2DM group and positively associated with adiposity markers, unfavorable lipid profile, insulin levels, and HOMA-IR, but no association with irisin was found. Given the favorable metabolic effects attributed to irisin, the low plasma levels found in children and adolescents with T2DM could exacerbate the inflammatory and metabolic imbalances and the intrinsic cardiovascular risk of this disease. We propose an "irisin-proinflammatory/anti-inflammatory axis" to explain the role of irisin as a metabolic regulator in obesity and T2DM.